DDS-type near-infrared light absorber enables deeper lesion treatment in laser photothermal therapy while avoiding damage to surrounding organs - Takahashi, Masataka; Fujishiro, Jun; Nomura, Shinsuke; Harada, Manabu; Hinoki, Akinari; Arake, Masashi; Ozeki, Eiichi; Hara, Isao; Satoh, Ayano; Tainaka, Takahisa; Uchida, Hiro-o; Morimoto, Yuji (Frontiers in Bioengineering and Biotechnology, 2024)
The efficacy of drug delivery system (DDS)-type near-infrared (NIR) absorbing agents in enhancing laser photothermal therapy is widely acknowledged. Despite the acknowledged efficacy, the therapeutic advantages of photothermal therapy using DDS-type NIR-absorbing agents over simple photothermal therapy without such agents have not been fully elucidated. This study was designed to investigate two primary objectives: firstly, the ability of DDS-type NIR-absorbing agents to induce cell death at greater depths within tumors, and secondly, their capacity to minimize collateral damage to adjacent healthy organs. To investigate these objectives, we employed a combination of indocyanine green lactosome-a DDS-type NIR-absorbing agent-and a precision-controlled laser hyperthermia system. An orthotopic neuroblastoma tumor model was used to closely simulate clinical conditions. The findings revealed that photothermal therapy using the DDS-type NIRabsorbing agent not only facilitates deeper penetration of cell death within tumors but also significantly mitigates thermal damage to surrounding healthy tissues, when compared to simple phototherapy without the agent. Furthermore, the combined treatment significantly prolonged the survival periods of the animals involved. This study is the first to analyze these therapeutic efficacies using quantitative data from an orthotopic tumor animal model and substantiated the potential of DDS-type NIR-absorbing agents to deepen the therapeutic impact of photothermal therapy while safeguarding vital organs, thereby enhancing overall treatment outcomes.